2009
DOI: 10.1002/glia.20909
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin polymerization‐promoting protein (TPPP/p25) is critical for oligodendrocyte differentiation

Abstract: TPPP/p25, a recently identified tubulin polymerization promoting protein (TPPP), is expressed mainly in myelinating oligodendrocytes of the CNS. Here we show that TPPP/p25 is strongly upregulated during the differentiation of primary oligodendrocyte cells as well as the CG-4 cell line. The microRNA expression profile of CG-4 cells before and after induction of differentiation was established and revealed differential regulation of a limited subset of microRNAs. miR-206, a microRNA predicted to target TPPP/p25,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
147
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(154 citation statements)
references
References 38 publications
7
147
0
Order By: Relevance
“…9). The specificity is further supported by the unique fact that the assembly of these two disordered hallmarks occurs exclusively at pathological conditions since in normal brain SYN and TPPP/p25 are expressed in neurons [57,58] and oligodendrocytes [9,59], respectively. Previously we showed that TPPP/p25, similarly to SYN, could be taken up by cells from the medium [35].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…9). The specificity is further supported by the unique fact that the assembly of these two disordered hallmarks occurs exclusively at pathological conditions since in normal brain SYN and TPPP/p25 are expressed in neurons [57,58] and oligodendrocytes [9,59], respectively. Previously we showed that TPPP/p25, similarly to SYN, could be taken up by cells from the medium [35].…”
Section: Discussionmentioning
confidence: 96%
“…TPPP/p25 is a Microtubule Associated Protein; its expression is finely controlled in the human brain [7][8][9]. It is an intrinsically disordered protein (IDP) without a well-defined 3D structure, whose middle, highly flexible CORE region is straddled by the unstructured Nand C-termini [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that both TPPP1 and TPPP3 can be found in adult brains of various mammals. The exact localization of TPPP3 in brain is not known but TPPP1 can be found physiologically in oligodendroglia not in neurons [21][22][23]. Whilst TPPP1 seems to be brain-specific, TPPP3 has been found in other tissues as well [24][25][26].…”
Section: Tppps Of the Zebrafish (Danio Rerio)mentioning
confidence: 99%
“…TPPP/p25 is being intensively studied due to its role in brain function and deregulation leading to synucleinopathies, a group of neurodegenerative disorders characterized by fibrillary aggregates of α-synuclein protein in the cytoplasm of selective populations of neurons and glia (Marti et al 2003;Orosz et al 2009). TPPP/p25 has also been recently shown to be critical for oligodendrocyte differentiation, where its downregulation inhibits differentiation and promotes cell proliferation (Lehotzky et al 2010).…”
Section: Introductionmentioning
confidence: 99%